Effects of Providing a Sensory Attractant Powder to Suckling Pigs in Late Lactation and After Weaning on Post-Weaning Pig Performance - M. R. Wensley; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jason C. Woodworth; Joel M DeRouchey; Denny McKilligan; Nathan Upah (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 28 litters (241 × 600, DNA) and 355 nursery pigs (241 × 600, DNA; initially 12.2 lb) were used in a 29-d trial (4 d pre-weaning and 29 d post-weaning). The trial was conducted to determine the effect of providing a sensory attractant powder (Baby Pig Restart APF; TechMix Global; Stewart, MN) to suckling pigs in late lactation and after weaning on post-weaning feed intake and growth. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of: 1) pre-weaning treatment (without or with powder); 2) post-weaning treatment (without or with powder); and 3) body weight category (light or heavy). Overall, pre-weaning powder application did not have a significant effect on piglet weaning weight (P= 0.485) or post-weaning growth performance. Likewise, post-weaning powder application had no effect on the growth performance of pigs after weaning. The percentage of pigs that lost weight in the first 3 d after weaning was reduced by approximately 20 percentage points when pigs were provided powder both pre- and post-weaning compared to the other three treatment combinations (P= 0.015). This interaction diminished by d 7 and no other treatment effects were observed for the percentage of pigs that lost weight after weaning. In summary, sensory attractant powder had limited effects on growth performance of pigs after weaning. However, sensory attractants may encourage activity around the feeder after weaning when pigs also receive the same sensory attractant pre-weaning, as indicated by the percentage of pigs that lost weight after weaning. More research is needed to better understand the implications of early sensory learning and its effect on subsequent feed intake.
Keywords: performance; pig; sensory attractant; suckling; weaning